Domesticating indigenous fruit trees as a contribution to poverty reduction - Schreckenberg, Kate; Awono, A.; Degrande, A.; Mbosso, C.; Ndoye, O.; Tchoundjeu, Z. (2006)
The contribution that domesticated indigenous fruit trees make to many farmers’ livelihoods is often not acknowledged in either national- or international-level poverty reduction strategies. Current agricultural data tend to be restricted to a narrow range of exotic fruit (e.g. mango, avocado, citrus). Existing data on indigenous fruit are often not presented in the kinds of income-related terms used in the policy debate, nor are they linked to simple policy recommendations. Drawing predominantly on the examples of Dacryodes edulis and Irvingia gabonensis in Cameroon and Nigeria, this paper presents evidence for the contribution of these fruit trees to poverty reduction. Evidence on the numbers and types of people obtaining an income from indigenous fruit trees, the proportion and value of that income and whether the income acts as a safety-net or can help to move people out of poverty, is presented. Non-income related impacts on health and the environment are also discussed. Finally, key policy interventions required to sustain and increase the already valuable contribution of domesticated indigenous fruit trees are outlined.